Impact of Mediated Intimate Interaction on Education: A Huggable Communication Medium that Encourages Listening - Nakanishi, Junya; Sumioka, Hidenobu; Ishiguro, Hiroshi (Frontiers in Psychology, 2016)
In this paper, we propose the introduction of human-like communication media as a proxy for teachers to support the listening of children in school education. Three case studies are presented on storytime fieldwork for children using our huggable communication medium called Hugvie, through which children are encouraged to concentrate on listening by intimate interaction between children and storytellers. We investigate the effect of Hugvie on children's listening and how they and their teachers react to it through observations and interviews. Our results suggest that Hugvie increased the number of children who concentrated on listening to a story and was welcomed by almost all the children and educators. We also discuss improvement and research issues to introduce huggable communication media into classrooms, potential applications, and their contributions to other education situations through improved listening.